Endpoints for clinical trials evaluating disease modification and structural damage in adults with Crohn's disease. - D'Haens, G; Fedorak, R; Lémann, M; Feagan, BG; Kamm, M; Cosnes, J; Rutgeerts, P; Marteau, P; Travis, S; Schölmerich, J; Hanauer, S; Sandborn, W (2009)
The management of Crohn's disease is rapidly changing. The advent of potent immunomodulatory and biologic therapies has led to more demanding endpoints for clinical trials than only clinical response and remission. Complete withdrawal of corticosteroids, healing of endoscopically visible lesions, and prevention of structural damage are only a few new endpoints that are finding their way into the clinical trials of today and those that are being developed for the future. Given the importance of selecting the most appropriate and relevant endpoints, the International Organization for Inflammatory Bowel Diseases (IOIBD) decided to develop guidelines that could be used by individual researchers, the pharmaceutical industry, and the regulatory bodies. The current document is to be read as a "position paper," which is the result of several years of discussion and consensus finding that was finally approved by the entire membership of the group. The proposed instruments will need further validation and standardization to demonstrate that they are reliable in stable disease and responsive to change, and to determine the cutoff points for response and remission.